Father Involvement in Infant Parenting in an Ethnically Diverse Community Sample: Predicting Paternal Depressive Symptoms - Bamishigbin, Olajide N.; Wilson, Dawn K.; Abshire, Demetrius A.; Mejia-Lancheros, Cilia; Dunkel Schetter, Christine (Frontiers in Psychiatry, 2020)
Early paternal involvement in infant care is beneficial to child and maternal health, and possibly for paternal mental health. The purpose of the present study was to examine the relationship between fathers’ involvement in early infant parenting and their depressive symptoms during the infant’s first year in a sample of 881 low-income Black, Hispanic, and White fathers recruited from five sites in the United States (urban, mixed urban/suburban, rural). Home interviews at one month after birth assessed three concepts based on prior research and community input: (1) father time spent with the infant, (2) parenting self-efficacy, (3) material support for the baby. Paternal depressive symptoms at 1, 6, and 12 months after the birth of a child were assessed with the Edinburgh Postpartum Depression Scale. Generalized estimating equations tested whether the three indicators of father involvement at one month after birth predicted lower subsequent paternal depressive symptoms controlling for social and demographic variables. Greater time spent with the infant, parenting self-efficacy, and material support were all significantly associated with lower paternal depressive symptoms during the first year. When risk of depression (scores > 9) was examined, only parenting self-efficacy among fathers was associated with higher likelihood of clinical depression. Findings have implications for future research on mechanisms linking paternal involvement and paternal mental health, and for possible paid paternal leave policies in the future.